(ADSORPTION STUDY OF HEAVY METAL CATION BY CARRAGEENAN FROM SEAWEED EXTRACT) - Kesumaputra Wiranegara, Raden
Carrageenan is a seaweed sap from certain species of red algae (rhodophyceae). Carrageenan consists of three types, namely kappa, iota and lambda. Carrageenan is often used as a emulgator or stabilizer in a variety of drinks or food. The extraction yield of carrageenan from seaweed in this experiment is 54.9%. Infrared spectrum of carrageenan from isolation indicate peaks at 3460.2 to 3606.2 cm-1 for the O-H group, 1670.4 cm-1 for S-O group and from 1140.1 to 1222.7 cm-1 for the C-O groups in accordance with expected structure of carrageenan. In this experiment, adsorption of heavy metal cation by carrageenan was studied. The concentration of heavy metal cations were optimally obtained at concentrations of less than 50 ppm and the optimum contact time on adsorption process in this experiment was 1 hour. Further experiments performed with the addition of two different types of acid, HCl and HNO3. The addition of HNO3 produced about 75% adsorption while the addition of HCl produced less than 10% adsorption to metal cations Cu(II) and Ni(II) but the cations Pb (II) had no absorption. The adsorption process for a solution mixture of three metal cations cations Pb(II), Cu(II) and Ni(II) did not affect the percent adsorption compared to the addition of HNO3 in the solution of a single heavy metal cations.